TINJAUAN ASPEK KEAMANAN DOKUMEN REKAM MEDIS DI RUANG FILLING RUMAH SAKIT ISLAM SITI KHADIJAH PALEMBANG: Dewi Nashrulloh (JURNAL SMART ANKes, 2021)
Security is the protection of one's privacy and the confidentiality of medical records. Medical record is a file containing records and documents regarding patient identity, examination, treatment, actions and other services that have been provided to patients. Medical record documents are confidential, information about diagnosis identity, disease history, examination history and patient medical history must be kept confidential by doctors, dentists, certain health workers, management officers and leaders of health care facilities. The purpose of this study was to determine the security aspects of files medical records in the filling room at Siti Khadijah Islamic Hospital Palembang. This research uses descriptive method. Collecting data in this study using interviews and observation. The data obtained were processed descriptively to describe the security aspects of medical record files in the filling room at Siti Khadijah Islamic Hospital Palembang. The results of the study in terms of physical security aspects. The lighting in the filling room is good, 2 fire extinguishers are available (Light Fire Extinguishers) but their placement is not appropriate, officers have not used drugs or camphor or camphor to protect files from termites and rat attacks. Officers who eat and drink in the filling room. The security of the medical record file from the content aspect has not been maintained because the door of the medical record room is not locked and the finger door lock tool is broken, and the officer has used a book to borrow medical record files.